TANGGUNG JAWAB PENGUSAHA PT. TRI PUTRA KHATULISTIWA TERHADAP KERUSAKAN BARANG DALAM PERJANJIAN PENGANGKUTAN PADA PENGUSAHA PT. DUA AGUNG DISTRIK UTAMA DI KOTA PONTIANAK - NIM. A1012191023, EGI ZULFANI (Fakultas Hukum Universitas Tanjungpura, 2024)
Abstrac PT. Dua Agung Distran Utama in this case is referred to as a service user handing over responsibility to PT. Tri Putra Khatulistiwa (as a service provider called Entrepreneur) so that goods sent through PT. Tri Putra Equator was able to get to their destination safely in good condition and on time. PT. Tri Putra Khatulistiwa, namely the workers must be able to keep the goods carried through their transportation services not damaged or delayed when they arrive at their destination. In carrying out its business PT. Tri Putra Khatulistiwa is managed by a businessman named Syahrul Raniandy and his brother and wife assisted by truck drivers and couriers as well as part of packing goods. Services provided by PT. Tri Putra Khatulistiwa is very satisfying considering that PT. Tri Putra Khatulistiwa must be able to compete with other service companies engaged in the same field, so that transportation needs can be met quickly and precisely. However, there are not a few problems faced by PT Entrepreneurs. Tri Putra Khatulistiwa, one of the problems faced is the damage to the property of PT Dua Agung Disran Utama, so that the Entrepreneur of PT. Tri Putra Khatulistiwa must compensate for losses according to the company regulations stated above.So the problem in this research is